DAMPAK VARIABILITAS CURAH HUJAN DAN KESESUAIAN LAHAN TERHADAP PRODUKSI KAKAO DI KABUPATEN PESAWARAN, LAMPUNG - Refki Sanjaya; Dimas Prakoswo Widiyani (Universitas Lampung, 2026)
Cocoa (Theobroma cacao L.) is a strategic plantation commodity contributing significantly to Indonesia’s economy. Pesawaran Regency, one of the cocoa production centers in Lampung Province, faces biophysical challenges related to rainfall variability and heterogeneous land-suitability conditions. This study aimed to analyze rainfall patterns and variability from 2016–2022, evaluate cocoa productivity trends, assess agroclimatic and land suitability characteristics, and examine the relationship between rainfall and cocoa productivity. The research was conducted in November–December 2024 using secondary data on annual rainfall, cocoa productivity (2016–2022), and land suitability parameters. Data were analyzed using descriptive statistics, land suitability evaluation, Pearson correlation, and simple linear regression. Results showed that annual rainfall ranged from 1,827–2,250 mm/year, remaining within the optimal range for cocoa cultivation. Productivity increased from 719 kg/ha (2016–2017) to 1,106 kg/ha (2018), stabilized at approximately 1,174 kg/ha (2019–2021), and declined to 876 kg/ha in 2022. Land suitability classes ranged from S1 to S3, with major limiting factors including acidic soil pH, low–moderate phosphorus availability, limited nutrient retention, and erosion risk. Correlation analysis revealed a very weak relationship between rainfall and productivity (r = –0.096; R² = 0.009) with the regression equation Y = 1266.94 – 0.135X. These findings indicate that cocoa productivity dynamics in Pesawaran Regency are more strongly influenced by land conditions and management practices than by annual rainfall variability.